Implementation of Quality improvement Strategies and Competitiveness in islamic educational institutions - Fadhli, Muhammad (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
The increasing public interest in Islamic Education Institutions has not been followed by efforts to improve the quality of Islamic Education Institutions (IEI). The quality of IEI will have an impact on its competitiveness. This research uses a qualitative method of literature type. The data collection technique starts from mapping, analyzing, and evaluating data from primary sources in the form of scholars' results of previous studies. The findings in this study are four main things that must be achieved or maintained by Islamic educational institutions to improve quality and have competitiveness: 1) Islamic educational institutions must have a high quality that follows the wishes of parents, government, and society in general. 2) Islamic educational institutions need to pay attention to and examine every customer response from Islamic educational institutions because the main goal is to provide satisfaction to customers of Islamic educational institutions (students, parents, government, and the world works). 3) Innovation is necessary because Islamic educational institutions can respond to changing times. Islamic education institutions must continue to innovate, including institutional innovation and management, curriculum innovation, learning innovation, innovation of learning facilities and infrastructure, and innovation by educators and education staff. 4) effectiveness and efficiency is the estuary of the management process.